EFFECT OF SUPPLEMENTATION OF WITHANIA COAGULANS FRUIT ON THE FASTING PLASMA GLUCOSE LEVELS OF TYPE 2 DIABETIC SUBJECTS - V, Hemalatha; Vigasini, Nora (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study is to determine the effect of supplementation of Withania coagulans fruit on the fasting plasma glucose (FPG) levels of type 2 diabetic subjects. Methods: In the natural system of medicine, many plants have been claimed to be useful for the management of diabetes mellitus. W. coagulans (Paneer poo) is one such source in which the fruit of the plant possesses hypoglycemic properties. The study was designed to determine the effect of a 60-day supplementation of W. coagulans fruit drink on the FPG levels of Type 2 diabetic subjects. W. coagulans fruit (6 numbers - approximately 2.5 g) was soaked overnight in 100 ml of water. This was administered to the experimental group. The control group received a placebo. Results: There was a significant decrease in the FPG levels of the experimental group on the 61st day. There was a statistically significant increase in the FPG level of the control group on the 61st day, showing that the placebo did not have any hypoglycemic effect. Conclusion: A significant reduction in FPG levels in the experimental group at the end of the study period proves that W. coagulans is a good hypoglycemic agent.